Estimating the Impact of the Balassa-Samuelson Effect in Central and Eastern European Countries: A Revised Analysis of Panel Data Cointegration Tests - Miletić, Mirjana (Panoeconomicus, 2012)
This paper aims to reassess the contribution of the Balassa-Samuelson effect to the inflation and real exchange rate appreciation using panel data for nine CEECs covering the period ranging from the mid-1990s to the third quarter of 2010. The main idea of this analysis is to answer the question of whether the Global Economic Crisis had a significant impact on the efforts of CEECs to stay on the path of real convergence. The Balassa-Samuelson effect explains less than 1.5 percentage points on average of inflation differential relative to the euro area and around 1 percentage point of the total domestic inflation. The results are robust across the model specification and estimation method. Most of the results point out that the Balassa-Samuelson effect has not changed considerably during the crisis even though it is lower compared to that in the earlier stage of transition (for the period up to 2004).Key words: Baumol-Bowen effect, Balassa-Samuelson effect, Real appreciation, Inflation.JEL: C52, E01, O11.